Automation of Air Humidity Monitoring and Control for Orchid Plants Using BME280 Sensor Based on IoT - Margareta, Regi Tia; Yoanda, Alya Putri; Rahma, Diana Mauli; Ayu, Jutira; Arsyad, Fitri (Journal of the Physical Society of Indonesia, 2025)
Air humidity is one of the important indicators in supporting the growth and development of plants. Mismatched humidity levels with plant needs can hinder their growth and cause root and stem rot. One type of plant that requires a certain humidity level is the Cymbidium orchid, which ideally needs air humidity between 60% and 80%. However, the fulfillment of this humidity requirement is generally still done manually, requiring time and human labor. To address this issue, an air humidity automation system is needed that can be monitored remotely to ensure the needs of the plants are met optimally. This study aims to design an Internet of Things (IoT) based air humidity automation system using the NodeMCU ESP32 microcontroller as the main control unit programmed through Arduino IDE software. This system has a BME280 sensor as a humidity detector and a mist maker as an actuator that produces cool mist to maintain humidity in the Cymbidium orchid planting space. The system monitoring is done remotely via the Blynk IoT application on smartphones. The research results show that this system successfully implemented the BME280 sensor in air humidity automation, with an average precision value of 98.91%, an accuracy of 98.98%, and an error rate of 0.076%.